'We just get a bit set in our ways': renewing democracy and solidarity in UK trade unions. (May 2020) - Connolly, Heather
In a broader context of austerity, sustained financial pressures and policies of restructuring and outsourcing have steadily eroded traditional features of UK public sector employment such as job security, fair reward and collective representation through trade unions. This article examines how a UK trade union representing local government workers attempted to respond more effectively to radical restructuring plans. By engaging in a process of democratic experimentation, full-time officials from above and activists from below sought to challenge the existing 'insider' relationship between branch officers and management, which was seen as ineffective in responding to a severe disruption in the regulation of local government employment. Drawing on participatory ethnographic research, the findings show the importance of leadership in the processes towards union renewal and the tensions and struggles underlying democracy and solidarity. Union renewal is presented here as a dialectical process and set of responses involving both strategic direction from above and membership pressure and activism from below.